2001
DOI: 10.1037/0022-3514.81.5.842
|View full text |Cite
|
Sign up to set email alerts
|

Social influence effects on automatic racial prejudice.

Abstract: Although most research on the control of automatic prejudice has focused on the efficacy of deliberate attempts to suppress or correct for stereotyping, the reported experiments tested the hypothesis that automatic racial prejudice is subject to common social influence. In experiments involving actual interethnic contact, both tacit and expressed social influence reduced the expression of automatic prejudice, as assessed by two different measures of automatic attitudes. Moreover, the automatic social tuning ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
376
5
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(410 citation statements)
references
References 79 publications
23
376
5
6
Order By: Relevance
“…18,19 Finally, it is possible that the interviews were influenced by the gender of the interviewer through social tuning. 27 Our study supports the existence of gender differences in residents' perceptions and experiences in directing patient care and indicates that further research may be useful in exploring how female residents successfully negotiate the interactions of prescriptive gender norms for behavior with a directive leadership position. The resulting insights may help promote the success and career satisfaction of all resi-dents.…”
Section: Resident Perceptions Of Influence 1619supporting
confidence: 75%
See 1 more Smart Citation
“…18,19 Finally, it is possible that the interviews were influenced by the gender of the interviewer through social tuning. 27 Our study supports the existence of gender differences in residents' perceptions and experiences in directing patient care and indicates that further research may be useful in exploring how female residents successfully negotiate the interactions of prescriptive gender norms for behavior with a directive leadership position. The resulting insights may help promote the success and career satisfaction of all resi-dents.…”
Section: Resident Perceptions Of Influence 1619supporting
confidence: 75%
“…1), 45% women and 87% white of European descent. The mean age was 28.2 years (range [23][24][25][26][27][28][29][30][31][32][33][34][35]. Nonresponders were more likely to be male or departing postgraduate year 3 (PGY-3) residents.…”
Section: Participantsmentioning
confidence: 99%
“…The current research is also the first to explore the effect of a public versus private setting on the IRAP, and the impact of reducing response latency. Consistent with previous IAT studies investigating contextual effects (e.g., Boysen et al, 2006;Lowery et al, 2001), we hypothesized that the public group would exhibit less racial stereotyping than would the private group. However, the public versus private manipulation in Experiment 1 had no significant impact on overall IRAP performance, and an effect opposite to that expected was found at the trial-type level.…”
Section: Discussionmentioning
confidence: 57%
“…The results showed that the public context significantly decreased the level of bias toward homosexuality relative to the private context. Critically, this finding suggests that the IAT may have some of the same drawbacks as explicit measures (see also Lowery, Hardin, & Sinclair, 2001;Richeson & Ambady, 2003).…”
mentioning
confidence: 99%
“…Essentially, salient positive information about a given category produces IAT scores indicative of more favorable evaluations. Such manipulations have involved exposure to movie clips that depicted Blacks at a harmonious family event versus an argumentative, gang-related scene (Wittenbrink, Judd, & Park, 2001), presentation of a series of either admired Black individuals and disliked Whites or disliked Blacks and admired Whites (Dasgupta & Greenwald, 2001), assigning participants to interact with a Black partner who occupied a superior or subordinate task role (Richeson & Ambady, 2003), exposure to violent and misogynous rap music (Rudman & Lee, 2002), and introduction to the IAT (specifically as a procedure for assessing prejudice) by a Black versus a White experimenter (Lowery, Hardin, & Sinclair, 2001). Yet, such findings do not constitute unambiguous evidence for the inference that automatically-activated attitudes have been modified.…”
Section: On the Presumed Malleability Of Automatically-activated Attimentioning
confidence: 99%